A comparison of two fuzzy-based systems considering node security in MANET clusters. (2017) - Alinci, Mirjeta; Inaba, Takaaki; Elmazi, Donald; Spaho, Evjola; Kolici, Vladi; Barolli, Leonard
A Mobile Ad Hoc Network (MANET) is a multi-hop wireless network in which the mobile nodes are dynamic in nature and which has a limited bandwidth and minimum battery power. Owing to this challenging environment the mobile nodes can be grouped into clusters to achieve better stability and scalability. Grouping the mobile nodes is called clustering, in which a leader node is elected to manage the entire network. In this paper, first we introduce various approaches for clustering focus on different performance metrics. Then, we show some clustering schemes. Finally, we present and compare two fuzzy-based systems (called F2SMC1 and F2SMC2) for improving the security of cluster nodes in MANETs. We compare the performance of F2SMC1 and F2SMC2 and show that the F2SMC2 is more complex than F2SMC1, but is more reliable and secure.